Pedagogical Studies at Kaunas University of Technology: A Case Study - Bankauskienė, Nijolė; Masaitytė, Ramunė (Vilnius University Open Series, 2020)
Recently, different opinions on teacher training in Lithuania have been increasingly heard during various meetings and conferences. This discussion was inspired by a number of challenges. Currently, the country is facing a considerable demographic problem: a declining number of pupils at schools, optimization of school network, and aging teaching staff. This reality has a direct impact on the training strategy of teachers. A current offer is to establish two teacher-training centres in Vilnius and Kaunas, and to connect the universities of Klaipeda and Siauliai to them. It has been noticed that more and more young people, who have graduated from higher education and want to work at schools, prefer one-year pedagogical studies, or even a double qualification degree instead of four years of full pedagogical studies. For this reason, there is an increasing interest in organizing pedagogical studies at Vilnius University and Kaunas University of Technology.